2005
DOI: 10.1097/00001813-200501000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Weekly paclitaxel and epirubicin in the treatment of symptomatic hormone-refractory advanced prostate carcinoma: report of a phase II trial

Abstract: The efficacy of weekly paclitaxel in androgen-independent prostate cancer and its addictive cytotoxicity with anthracycline derivatives led us to determine the safety and efficacy of a weekly schedule of paclitaxel and epirubicin. Between October 2000 and November 2002, 32 patients were enrolled in this study. Patients characteristics included a median age of 72 years (range 68-77), adequate hepatic, cardiac, renal and bone marrow functions, ECOG performance status of 1-2, and no prior chemotherapy. All patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Of 16 published phase II studies, Paclitaxel was combined with Carboplatin, Estramustine, Etoposide, and Epirubicin [46,[47][48][49][50][51][52][53][54][55][56][57][58][59][60]. There are synergistic in vitro data of the combination of Paclitaxel and Gemcitabine [61].…”
Section: Paclitaxel Combinations For the Treatment Of Hrpcmentioning
confidence: 99%
“…Of 16 published phase II studies, Paclitaxel was combined with Carboplatin, Estramustine, Etoposide, and Epirubicin [46,[47][48][49][50][51][52][53][54][55][56][57][58][59][60]. There are synergistic in vitro data of the combination of Paclitaxel and Gemcitabine [61].…”
Section: Paclitaxel Combinations For the Treatment Of Hrpcmentioning
confidence: 99%
“…Combination of DOC with other drugs has been developed for the treatment of PCA (Scheme 1). Studies have indicated that anthracyclines can enhance the inhibitory effect of DOC against PCA (Pienta, 2001;Kouroussis et al, 2005;Mackler and Pienta, 2005;Neri et al, 2005;Petrioli et al, 2007;Neri et al, 2009). Several studies have verified that the combination of DOC with DOX has a synergistic effect in the treatment of PCA.…”
Section: Discussionmentioning
confidence: 99%
“…DOC remains the mainstream therapeutic agent for PCA treatment and is combined with other drugs, including mitoxantrone and estramustine, to treat PCA (Sinibaldi et al, 2002;Petrylak et al, 2004). Several clinical studies have demonstrated that DOC combined with anthracyclines could increase the anti-PCA effect because anthracyclines would enhance the sensitivity of the PCA cells to DOC (Pienta, 2001; Kouroussis et al, 2005;Mackler and Pienta, 2005;Neri et al, 2005;Petrioli et al, 2007;Neri et al, 2009). DOX is a kind of anthracycline that can prevent DNA remodeling (Pommier et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, although the combination of mitoxantrone plus ketoconazole needs to be studied further, existing data support the notion that there is an added benefit to combining these 2 agents. It also should be noted that epirubicin has an activity spectrum similar to that of doxorubicin and can be well tolerated and active in hormone-refractory prostate cancer, 35,36 and therefore also may be suitable in combination with ketoconazole.…”
Section: Discussionmentioning
confidence: 99%